A Statistical Overview of Death due to Alcohol Poisoning in the Rajshahi Region - Uddin, Md Kafil; Royhan, Zaman Nishat; Sumaiya, Shirin; Sadat, Md Alvi; Chatterjee, Nibedita (TAJ: Journal of Teachers Association, 2023)
Introduction: The prevalence of death due to alcohol poisoning is increasing at an alarming rate in Bangladesh. However, there is a lack of actual statistics regarding death cases due to alcohol poisoning in the Rajshahi region. Therefore, this study was designed to explore the recent statistical report of death cases due to alcohol poisoning in the Rajshahi region. Methods: The Department of Forensic Medicine & Toxicology, Rajshahi Medical College, Rajshahi, Bangladesh, conducted this statistical study, reporting 29 deaths between January 2019 and September 2021. The data was collected from the documents stored in the Department of Forensic Medicine & Toxicology. Results: This study elucidates that the incidence of death due to alcohol poisoning is increasing over time. Ninety-three percent of victims were male. The maximum number of deaths (34.5%) due to alcohol poisoning was found in people between 21 and 30 years old. The maximum number of victims (27.59%) in the profession were students. Around two-thirds of the deceased were married. Only 24% of victims were other than Islam religion. Conclusion: As the rate of death due to alcohol poisoning increases over time, it might indicate an increasing number of alcohol consumers. Besides, the lack of consciousness is associated with unwanted death. TAJ 2022; 35: No-2: 119-124